Isolated Sporadic Morning Glory Syndrome A Rare Entity - Priya Dua; Amar Dev; Akash Dua (Delhi Journal of Ophthalmology)
Morning Glory syndrome is diagnosed by whitish glial tissue at the bottom of the disk with retinal blood vessels emerging from the periphery of the excavation in a radial pattern. Morning glory syndrome has a spectrum of severity, with most patients retaining useful vision. It is usually known to be unilateral. We report an unusual case of a bilateral form of the disorder with an aim to distinguish it from other bilateral optic nerve head anomalies.